KELAYAKAN INVESTASI USAHA DAN KEEKONOMIAN BIODIESEL - Zulkifli Rangkuti; Bambang Mulyana (University of Merdeka Malang, 2014)
This study aimed to analyze the business feasibility and economy of the biodiesel industry in terms of variousaspects with various assumptions. Main calculation techniques used were: the benefit and cost ratio (B/CRatio), the net present value (NPV), internal rate of return (IRR), and payback period (PBP). Assuming aninstalled capacity of 100,000 tons per year, the production of biodiesel could be produced in the third year,90,278 tons per year. The production increased steadily until 92,778 tons per year from the fourth year to thetenth year. It can be achieved by general assumption that working days within 1 year, from January toDecember were 360 days. Economy of biodiesel would happen if the subsidy could cover the difference betweenthe selling price of biodiesel and MOPS diesel fuel prices. In 2011, the average value of subsidy was Rp2,463.60per liter, but because the rule stated that the maximum subsidy was Rp2,000.00 per liter, the governmentpurchase on biodiesel products was Rp8,840.00 per liter, which was calculated based on diesel fuel MOPS in2011 as much as Rp6,840.00 per liter plus maximum subsidy. The result of analysis showed that biodieselinvestment was worthy to be realized.